A Facile and Fast Gelation Process to Prepare Highly Spherical Millimeter‐Sized Silica Aerogel Beads. (24th April 2015) - Yu, Yuxi; Guo, Deqian; Fang, Jiyu
Abstract : Millimeter‐sized silica aerogel beads were successfully prepared by a facile fast gelation process, in which silica sol beads were generated by extruding preformed silica sol through multiple nozzles into oil phase and then transformed into silica alcogel beads, followed by supercritical drying. The transition process from the silica sol to the silica alcogel beads was finished at a 97.6% conversion rate. The resultant silica aerogel beads have an average diameter of ~1.5 mm with a good sphericity, and an average pore size of ~12 nm with topical porous three‐dimensional network structures.